PROFESSOR VLADIMIR MIKHAILOVICH TAVROVSKY IS A DOCTOR AND SCIENTIST WHO WAS AHEAD OF TIME BY HALF A CENTURY - Аркадий Лейбович Ханин (Медицина в Кузбассе, 2024)
It is difficult to imagine modern medicine without digital technologies, without automated workplaces for doctors of polyclinics, hospitals, prevention and rehabilitation centers. Unfortunately, these new technologies often do not facilitate, but complicate the work of a doctor, require additional filling out of documents, and do not provide feedback to the main actor in healthcare – the attending physician. Many modern information systems are created by specialists in the field of programming, and their main task is to collect information, not help in making decisions at every single moment of a complex medical and diagnostic process. These contradictions have been eliminated in the system created by Professor V.M. Tavrovsky, implemented in 80 different medical institutions in 11 cities of Russia. At the same time, the main user – doctor received not only a clear algorithm of actions in a specific clinical situation, but the system showed the priorities of decision-making, the responsibility of each of the members of the management chain: from the attending physician (district doctor), to the chief physician and the head of health care of the city or region.